Penerapan Aplikasi Quizizz Dalam Kegiatan Cerdas Cerman Pada Siswa SMP AL Furqon Jember - Indah Rahayu Panglipur; Denok Mugi Hidayanti; Farida Isnaini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
AL Furqon Jember Junior High School students received guidance in applying the Quizizz application through quizzing activities. This effort aims to increase students’ learning motivation, provide knowledge, and reveal their potential. During the Mid-Semester Activities (MTS), guidance was carried out through discussion, practice, as well as providing material in the form of quizzes directly from the Quizizz application. Students can easily understand the technique of using this application because the tools used are easy and flexible, with laptops, LCDs, and projectors available at school. The results of this quizzing activity are in the form of general knowledge questions that students must answer through multiple choices quickly. At the end.